1995
DOI: 10.1128/iai.63.11.4231-4237.1995
|View full text |Cite
|
Sign up to set email alerts
|

The two distinct phospholipases C of Listeria monocytogenes have overlapping roles in escape from a vacuole and cell-to-cell spread

Abstract: Listeria monocytogenes secretes two distinct phospholipases C, a phosphatidylinositol-specific phospholipase C (PI-PLC) and a broad-range phospholipase C (PC-PLC). In this study, single in-frame deletion mutants with mutations in each PLC and a double mutant lacking both PLCs were characterized with regard to virulence in mice, escape from a primary vacuole, and cell-to-cell spread in cell culture. The mutant lacking PI-PLC, previously shown to be twofold less virulent than the wild type in mice, had a minor d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
226
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 401 publications
(241 citation statements)
references
References 47 publications
14
226
1
Order By: Relevance
“…The majority of wildtype L. monocytogenes escape the vacuole within the first 30 minutes following entry, however Py et al (2007) assayed escape at four hours post-infection [44]. Since L. monocytogenes begin to spread from cell to cell as early as three hours post-infection and phospholipase mutants have a known defect in escape from a secondary vacuole, it is possible that the defect in growth observed by Py et al (2007) was due to a defect in escape from vacuoles of secondarily infected cells [13,45,46] Autophagy plays a role in cellular homeostasis. For example, smooth ER, excess peroxisomes, damaged mitochondria and rough ER have been shown to be selectively targeted and removed from cells by the autophagic machinery [47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of wildtype L. monocytogenes escape the vacuole within the first 30 minutes following entry, however Py et al (2007) assayed escape at four hours post-infection [44]. Since L. monocytogenes begin to spread from cell to cell as early as three hours post-infection and phospholipase mutants have a known defect in escape from a secondary vacuole, it is possible that the defect in growth observed by Py et al (2007) was due to a defect in escape from vacuoles of secondarily infected cells [13,45,46] Autophagy plays a role in cellular homeostasis. For example, smooth ER, excess peroxisomes, damaged mitochondria and rough ER have been shown to be selectively targeted and removed from cells by the autophagic machinery [47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…The wild-type Listeria monocytogenes strain used was 10403S [54]. The Dhly (DP-L2161; [55]), DactA (DP-L3078; [56]) and DplcAB (DP-L1936; [46]) mutants contained in-frame deletions of the respective genes in the 10403s background.…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…The combined action of phospholipase and a pore-forming protein in escape from the vacuole is also seen for the well-studied L. monocytogenes, an intracellular pathogen that replicates in the cytosol of host cells [63,64]. After invasion into cells, L. monocytogenes escapes from its vacuole by the combined action of the pore-forming protein listeriolysin O (LLO) and a phosphatidylinositol-specific PLC (PI-PLC), both secreted by the bacterium [63,64,66,67]. It has been suggested that LLO forms holes into the vacuole membrane, which allow L. monocytogenes phospholipase to access exposed membrane leaflet [63].…”
Section: Phospholipases and Vacuolar Membrane Damagementioning
confidence: 98%
“…After such cell-to-cell spread the bacterium resides in a secondary vacuole surrounded by a double membrane. The escape from this double-membrane vacuole requires the coordinated action of LLO, PI-PLC and PC-PLC (a PC-preferring PLC also secreted by L. monocytogenes) [67,69,70]. Recent data indicate that the PI-PLC and PC-PLC act specifically in the initial degradation of the inner membrane of the double-membrane vacuole, after which the outer membrane is disrupted by LLO [71].…”
Section: Phospholipases and Vacuolar Membrane Damagementioning
confidence: 99%
“…Listeria monocytogenes escape is enhanced by two bacterial C-type phospholipases, termed PlcA and PlcB (Smith et al ., 1995). Lm mutants deficient in a phosphatidylinositol-specific phospholipase C (PlcA), escape from vacuoles less frequently than wild-type Lm (Smith et al ., 1995).…”
Section: Introductionmentioning
confidence: 99%